Elementos de estrutura e governança das parcerias entre o setor público e o setor privado : estudo de caso sobre o Programa Água Para Todos - Assis, Marilia Camara de (Universidade Federal de São Carlos, 2016)
In the past few decades, following the growing trend to create partnerships between public and private sectors in multiple countries, this topic has been broadly discussed in global academic production. The main purpose of this research is to identify potential relationships in those partnerships’ structure, how they are handled, and the results they aim to achieve. For that matter, this paper presents an overview of the subject, taking into account the context of emergence and development of those partnerships in Brazil and in the world, the different terminologies and concepts used to discuss them, and the multiple possibilities to characterize them. Three aspects were considered for the characterization, namely: 1) the partnerships’ hardware, composed by their standards, constitution and objectives – its physical structure; 2) the partnerships’ software, or how their members relate to one another, to other actors, to their organizations, to society, and to the public and private systems that surround them – its governance; and 3) the results aimed by partnerships. The government program Água Para Todos (APT), one of the measures for the governmental plan Brasil sem Miséria (BSM) – a strategy by the Federal Government (2011-2014), which aims to overcome extreme poverty in Brazil – was selected to approach this theme and to illustrate the rationale behind partnerships between public and private sectors. In the form of different arrangements to achieve the objective of making the access to water universal in the Brazilian semi-arid region, the participation of actors from public and private sectors joining efforts and taking turns on different roles was critical to assure that the goals established by the Federal Government were fulfilled and to foster other benefits for the population as well. It was also possible to observe that the three aspects of partnerships considered for the analysis affect one another. Just as the partnership’s hardware affects its governance, any kind of obstacle faced by the form of operation might result in changes to the previously constituted structural elements. The possibility to reassess the continuous forms of partnerships’ hardware and software might be one of the requirements to achieve the best possible results. At the same time, tracking results along the partnership execution might point to difficulties and bottlenecks which, occasionally, would act as guides to the required changes to its structure and governance.
Keywords: Parcerias público-privada; Água Para TodosÁgua Para Todos; Governança; Public-Private Partnerships; Government Program; Governance; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO::PROCESSOS DE TRABALHO